NORFOX: An Experimental Fibre-Optic DAS Array for Seismo-Acoustic Monitoring in Norway - Antoine Turquet; Andreas Wuestefeld; Alan F. Baird; Kamran Iranpour; Anna Maria Dichiarante; Sindre Stokkan; Ravn Rydtun; Volker Oye; Ben D. E. Dando; Andreas Köhler; Sven Peter Näsholm (Pure and Applied Geophysics, 2026)
Distributed Acoustic Sensing (DAS) is a rapidly developing technology providing spatially dense data of great value for seismic and acoustic monitoring. This paper presents NORFOX, a dedicated DAS installation in southeastern Norway. NORFOX comprises a dedicated fibre-optic array with a geometry designed for earthquake and explosion monitoring. A defining feature of the site is its co-location with the NORES seismic and infrasound arrays, enabling direct comparison of DAS observations with conventional seismic and acoustic measurements. This multi-sensor configuration provides a controlled environment for benchmarking DAS data, and it paves the way for advanced, multi-physics wavefield modelling. NORFOX records various natural and anthropogenic seismo-acoustic signals, including earthquakes, explosions, aircraft, and thunder. The ultra-dense spatial sampling provided by DAS can complement traditional monitoring networks, including those used for nuclear-test monitoring. NORFOX helps address key challenges in small-yield event detection, phase discrimination, and event classification. We describe the DAS array layout, the design rationale, the co-located instrumentation, and provide an initial characterisation of fibre performance and background noise behaviour. We also discuss practical aspects of operating the site and outline current limitations. The site is further complemented by an all-sky camera and weather station to record visual events such as meteoroids and lightning activity, and to measure environmental changes; both of which can support the interpretation of the DAS measurements. Using representative examples, we demonstrate the capability of NORFOX for DAS-based array analysis and benchmarking against conventional arrays. NORFOX therefore provides a valuable test-bed for developing, validating and comparing future DAS monitoring approaches in seismology and seismo-acoustic sensing.